Principles of Entrepreneurship (ENT530): Business Model Canvas: Bottlistic / Afifah Nazaruddin … [et al.] - Nazaruddin, Afifah; Abu Hanifah, Norfatihah; Kasmiri, Nur Fathehah Farhana; Samsul Nizal, Nur Salsabila; Farhana, Dea Shik; Samsor, Muhammad Izzuddin (2021)
Our company is called Dillaf Sdn. Bhd. And focus on the production of insulated water bottles. The reason for us to venture into this industry is we see the potential of our business to be able to grow even more because the products we produce can benefit consumers and get high demand from athletes. When we think of our competitors, there is a concern to us because now we need to focus on improving our products, our services, shipping and marketing. We are aware of society’s perceptions and views on this matter, so along the way we aim to educate people more about the products we produce and their benefits. For general knowledge, the human body is 50% water and 90% lazy. Sure, it’s important to stay hydrated, but keep using the tap to refill the 5-oz on an ongoing basis. a glass of water is not on the card. We test the best insulated water bottles so you can maintain a constant supply of water - at the cool temperatures demanded by summer days - by your side throughout the day. And because the insulation cuts both ways, we thought we could also test the bottle’s ability to make sure hot drinks stay hot in addition to cold cold drinks.